Development of the Structure of the Jamie Nurul Iman Sukaraja Mosque Building Based on the Needs of Congregation Facilities - Lutfi, Muhamad; Chayati, Nurul; Rulhendri, Rulhendri; Jodi Sumarno, Ajie (ASTONJADRO, 2023)
Jamie Nurul Iman Mosque has an area of 208.39 m2, the mosque building currently has limited facilities, such as parking facilities for worshipers who still use the shoulder of the road and ablution facilities and special toilets for men and women must be separated, efforts to complete the facilities for the congregation then it is necessary to develop the building, due to the limited land owned, the development is carried out vertically into three floors. The research was conducted by testing the concrete quality (f'c) of existing columns, beams and slabs, the concrete quality values were obtained sequentially of 13.6 MPa, 11 MPa and 11.2 MPa, then modeled the existing structure using the ETABS application and the results showed that column structure, beams experiencing over strength (O/S) cannot withstand the loads acting on the building, so the existing building structure cannot be used for the development of a new three-story mosque building. The results of the structural analysis of the plan based on SNI obtained the dimensions of the new mosque building with a size of 11.25 meters x 18.8 meters, reinforced concrete structures, non-concrete roofs and enamel domes. The material specifications for the new mosque structure are concrete quality (f'c) 30 MPa, reinforcing steel quality (fy) 400 MPa and 280 MPa (BJTP). Column dimensions are 50x50 cm (first floor), column 40x40 cm (second and third floors), main beam dimensions are 30x60 cm, main beam is 30x50 cm, and child beams are 25x40 cm, floor slab thickness is 15 cm, roof slab is not 13 cm thick. The first floor is equipped with male ablution facilities with an area of 12.51 m2, female ablution facilities with an area of 9.7 m2, toilet facilities with an area of 2.84 m2, and vehicle parking facilities with an area of 99.93 m2. The second floor is equipped with men's prayer facilities with an area of 102.87 m2, book storage facilities with an area of 10.5 m2, logistics facilities with an area of 5.67 m2. The third floor is equipped with women's prayer facilities with an area of 72.9 m2. The budget plan for the construction of a three-story new mosque concrete structure is Rp. 717,990,500.00.